Impact of improved technologies on production of sesame in Jaipur (III a Zone) district of Rajasthan - Babu Lal Yadav; Irfan Khan (Annals of Agricultural Research, 2024)
Krishi Vigyan Kendra, Chomu (Tankarda), District-Jaipur (Rajasthan) conducted cluster front line demonstrations (CFLDs) on sesame crop during Kharif 2020 and 2021. Total number of 125 demonstrations were conducted in an area of 50 ha by the active participation of farmers in Jaipur district of Rajasthan. The improved technologies such as improved variety, seed treatment, weed management, nutrient management and plant protection measures were demonstrated under the CFLDs. The results of CFLDs observed that the maximum average yield in two years (6.66 q/ha) was recorded in demonstration plot and the minimum yield (4.86 q/ha) was recorded in farmers practices. The highest average net returns (`30448/ha) was recorded in the demonstration plot as compared to farmers’ practice (`19883/ha). The maximum B:C ratio (2.82) was recorded in the demonstrated plot and minimum B:C ratio (2.37) was recorded in farmer practices.